Satisfaction of immediate or delayed switch to paliperidone palmitate in patients unsatisfied with current oral atypical antipsychotics. (November 2015) - Kwon, Jun Soo; Kim, Sung Nyun; Han, Jaewook; Lee, Sang Ick; Chang, Jae Seung; Choi, Jung-Seok; Lee, Heon-Jeong; Cho, Seong Jin; Jun, Tae-Youn; Lee, Seung-Hwan; Han, Changsu; Lee, Kyoung-Uk; et al.
<x xml:space="preserve">Abstract</x> Patient satisfaction with treatment is an important clinical index associated with the efficacy and adherence of treatment in schizophrenia. Although switching from oral antipsychotics to the long-acting injectable formulation may improve convenience, patient satisfaction has not been studied extensively. We carried out a 21-week, multicenter, randomized, open-label comparative study. A total of 154 patients with schizophrenia unsatisfied with current oral atypical antipsychotics were assigned randomly to either immediate or delayed switching to paliperidone palmitate, the long-acting injectable formulation of paliperidone. The Medication Satisfaction Questionnaire (MSQ) and the Treatment Satisfaction Questionnaire for Medication (TSQM) were used to evaluate patient satisfaction with treatment, whereas the Positive and Negative Syndrome Scale (PANSS) and the Personal and Social Performance (PSP) scale were used to evaluate efficacy. From baseline to the final assessment, the MSQ score increased significantly in both groups, and the increase was greatest after the first administration of paliperidone palmitate in the immediate switch group. The scores of TSQM effectiveness, convenience, and global satisfaction as well as the PSP total score increased significantly, whereas the PANSS total score decreased significantly in both groups. The immediate switch group showed a significant improvement in the TSQM convenience score compared with the delayed switch group on oral antipsychotics during the comparison period. Most adverse events were minor and tolerable. In short, switching from oral atypical antipsychotics to paliperidone palmitate because of poor satisfaction significantly improved patient satisfaction, with comparable efficacy and tolerability.